On the Stability of Graphene-Based Aqueous Dispersions and Their Performance in Cement Mortar - Teresa Gerace; Sebastiano Candamano; Simone Bartucci; Carlo Poselle Bonaventura; Alfonso Policicchio; Raffaele Giuseppe Agostino; Milena Marroccoli; Antonio Telesca; Mariano Davoli; Andrea Scarcello; Lorenzo S. Caputi; Daniela Pacilè (Applied Sciences)
Cement composites containing different carbon nanomaterials, namely graphene technical grade, graphene super grade, and graphene oxide, up to 1.0% by weight of cement, were prepared. Ultrasonic, chemical, and thermochemical treatments were applied to improve the stability of the dispersions containing the graphene-based nanomaterials. Their exfoliation was analyzed using Raman spectroscopy, and the stability of the dispersions was quantitatively investigated by means of the static multiple light scattering (SMLS) technique. The sonication process enhanced the intensity of the 2D band of graphene technical grade, suggesting a partial degree of exfoliation, while the hydrothermal treatment with sodium cholate significantly promoted the stability of its dispersion. The effect of the addition of selected graphene-based nanomaterials in mortars was evaluated in terms of fresh state properties, mechanical strength, capillary water absorption, and pore size distribution. Workability decreased with the increase in the amount of carbon nanomaterials. Field emission scanning electron microscopy (FESEM) was also employed to characterize the microstructure of pristine graphene-based nanomaterials and their inclusion within the cement matrix. Our results suggest that mechanical properties are only moderately affected by the inclusion of all additives, whereas the introduction of graphene significantly influences the coefficient of capillary water absorption. Specifically, a reduction of about 20% in the capillary water absorption coefficient was observed at the concentration of 1.0 wt% of graphene technical grade, which is ascribed to a refinement of the porosity.